2019
DOI: 10.1107/s2053229619012567
|View full text |Cite
|
Sign up to set email alerts
|

Unusual structure of a biphenyl fragment: the important role of weak interactions

Abstract: 1,5-Bis([1,1 0 -biphenyl]-4-yl)-5-hydroxy-3-methylheptane-1,6-dione, C 32 H 30 O 3 , was investigated by X-ray analysis, quantum chemical calculations and AIM (atoms in molecules) analysis. It was shown that four intramolecular C-HÁ Á Á forces are established between the two biphenyl fragments. C-HÁ Á Á interactions lead to a bending of the biphenyl part. The energy of the intramolecular interactions was estimated and the exclusive role of the moment of force was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, even the HCl-mediated interaction in 10 did not seem optimal (Figure ). To get engaged in such an interaction (HCl-mediated), the A-ring got significantly twisted (60°) toward the amide bond, whereas the biaryl group was unusually bent (10°) and the two phenyl rings displayed a somewhat lower torsion angle than usual (24°). Of course, such a conformation could also be caused by crystal packing; nevertheless, it clearly demonstrated that the rigidity of the amide group made it difficult in 10 to bring the two charged groups into close proximity of 4 Å as required for a productive electrostatic interaction …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, even the HCl-mediated interaction in 10 did not seem optimal (Figure ). To get engaged in such an interaction (HCl-mediated), the A-ring got significantly twisted (60°) toward the amide bond, whereas the biaryl group was unusually bent (10°) and the two phenyl rings displayed a somewhat lower torsion angle than usual (24°). Of course, such a conformation could also be caused by crystal packing; nevertheless, it clearly demonstrated that the rigidity of the amide group made it difficult in 10 to bring the two charged groups into close proximity of 4 Å as required for a productive electrostatic interaction …”
Section: Results and Discussionmentioning
confidence: 99%